2004
DOI: 10.1038/labinvest.3700002
|View full text |Cite
|
Sign up to set email alerts
|

Specific modulation of calmodulin activity induces a dramatic production of superoxide by alveolar macrophages

Abstract: Airway inflammation is a characteristic feature in airway diseases such as asthma and chronic obstructive pulmonary disease. Oxidative stress, caused by the excessive production of reactive oxygen species by inflammatory cells like macrophages, eosinophils and neutrophils, is thought to be important in the complex pathogenesis of such airway diseases. The calcium-sensing regulatory protein calmodulin (CaM) binds and regulates different target enzymes and proteins, including calcium channels. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…In the present study, no effect of nicardipine and BAPTA-AM and inhibitory effect of calmodulin antagonists suggest that the 7-ketocholesterol-induced oxidative stress may be mediated by calmodulin rather than changes in intracellular Ca 2+ levels. It has been shown that alveolar macrophages stimulated via Ca 2+ /calmodulin pathway produce high amounts of ROS [47]. In relation to this result, the current data indicates that calmodulin antagonists seem to prevent the 7-ketocholesterol-induced oxidative stress through the inhibitory action against the ROS formation process mediated by Ca 2+ /calmodulin.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, no effect of nicardipine and BAPTA-AM and inhibitory effect of calmodulin antagonists suggest that the 7-ketocholesterol-induced oxidative stress may be mediated by calmodulin rather than changes in intracellular Ca 2+ levels. It has been shown that alveolar macrophages stimulated via Ca 2+ /calmodulin pathway produce high amounts of ROS [47]. In relation to this result, the current data indicates that calmodulin antagonists seem to prevent the 7-ketocholesterol-induced oxidative stress through the inhibitory action against the ROS formation process mediated by Ca 2+ /calmodulin.…”
Section: Discussionsupporting
confidence: 62%
“…The calcium sensing regulatory protein calmodulin binds and regulates different target enzymes and proteins, including calcium channels, which modulate ROS in inflammatory cells 29 . To inhibit generation of the superoxide anion, the calmodulin antagonist W13 was used, and the effect was an almost total inhibition of intracellular ROS as measured by fluorescent rhodamine 123.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, observed age-dependent declines in CaM function and abundance may relate to observed declines in immune function ( 2 , . However, the downregulation of CaM function through the addition of inhibitors and binding peptides can also activate macrophages and block bacterial infections ( , ), suggesting a multifactorial role for CaM in mediating macrophage activation and bacterial killing.…”
mentioning
confidence: 99%